Analisis Pengurangan Emisi Melalui Penggunaan Kendaraan Listrik di Universitas Jember - Tika Kumala Sari (JUSTER : Jurnal Sains dan Terapan, 2025)
The climate change crisis that occurs in all parts of the world has become a trending topic in every discussion at various meetings of state officials. Lately, the world community, especially in Indonesia, has seen and felt the many abnormalities in each season and the many disasters that arise as a result of climate change. President Joko Widodo's submission at the 2021 UN Climate Change Conference (COP26) forum in Glasgow, Scotland targets Indonesia Net Zero Emission (NZE) in 2060 and is supported by Indonesian Presidential Instruction Number 7 of 2022 concerning the Use of Battery-Based Electric Motorized Vehicles as Operational Service Vehicles and / or Individual Service Vehicles for Central Government Agencies and Regional Governments. The purpose of this study was to determine how much the amount of emissions that can be reduced in each use of electric vehicles in the University of Jember area. The research method used is a literature study by collecting secondary data from articles, journals and other reliable literature. Secondary data used includes the number of employees of the University of Jember and motor vehicle emissions. The results showed that emissions generated from motorized vehicles by all employees of the University of Jember reached 6,742,553 kg.CO2 per year which could continue to increase along with the increase in motorized vehicles. The conclusion of the research is that one of the efforts to reduce emissions generated from conventional vehicles is the transition of motorized vehicles to electric vehicles that can support a significant reduction in carbon emissions in the campus environment. Therefore, policies are needed that encourage the use of electric vehicles as the main mode of transportation in the campus environment.